The Influence of Compensation and Commitment on Employee Performance at the Immigration Office Class I TPI Jambi - Sumarni Sumarni; Nurul Lathifah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study is to describe and investigate employee compensation and performance initiatives in Immigrant Class I Jambi. The analysis methods used here are quantitative analysis methods, observation, questionnaire, and documentation data collection techniques. In this study, the total population and sample of employees at Jambi Immigration Office was 81 people. This study uses a saturation sampling technique. The data analysis techniques used in this study included descriptive range analysis and multiple linear analysis using SPSS 21 software, and the results of the statistical analysis showed that compensation (X1) has a positive significance on employee performance. It shows that it has a significant impact. Personal commitment (X2) has a positive and significant impact on employee performance. At the same time, rewards and engagement have a positive impact on employee performance. Therefore, the results of this study show that improving employee performance is closely linked to rewards (direct and indirect rewards) and commitment, especially the highly compensated work itself (affective commitment, continuance commitment, normative commitment). We can conclude that they are related. It becomes easier to improve employee performance.